Analisis Faktor yang mempengaruhi Niat Wanita Pasangan Usia Subur untuk Papsmear di Wilayah Kelurahan Kedungmundu Wilayah Puskesmas Kedungmundu Kota Semarang - Elisa Ulfiana (JURNAL KEBIDANAN, 2013)
Background: Cervical cancer is an important health problem for woman worldwide.this is second type of most common cancer in woman,and experienced by more than 1,4 million woman worldwide. Method: This research is explanatory research.with approach uses cross sectional. The population is fertile female copuple of 1323 people.this research using proportional random sampling technique with sample of 307..relationship analysis done by using chi squere,and multivariate analysis using logistic regression analysis. Result: The results also indicated that the variable effective responses from woman of reproductive age couples have the strongest influence on the intention to couples of reproductive age woman,woman are good with effective responses OR 1,855 means that the effective responses are good to have a change to intention papasmear 1.855 time.suggestions for primary health care in order to,conduct health education to people regulary and activation of the cadres who have not maximally active.